TYPES OF NOBLE-METAL MINERALIZATIONS AND TYPOMORPHISM OF ORE MINERALS OF TYMOPHIYIVSK ORE MANIFESTATION (INGULSK BLOCK, UKRAINIAN SHIELD) - HRINCHENKO, O.; BONDARENKO, S.; SOMKA, V.; IVANOV, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
This paper discusses some features of formation of noble-metal (gold – arsenic and copper – silver) mineralization types of Tymopheevsk ore-manifestation, as typical gold object of Ingul’sk block of the Ukrainian Shield. It has been established, that despite of that fact, that gold – arsenic and copper – silver mineralization have been discovered in the same boreholes, conditions of their formation and localization in most cases are not not coincide.